Implementación de un infochannel utilizando servicios web para la visualización de contenido multimedia para el Sis Ecu 911 de la ciudad de Loja. - Cartagena Soto, Luis Alberto (2019)
Today, multimedia content dissemination services through data networks have a great reception in society. These types of mechanisms, since their conception and as they have been developed, have played a very important role within the ambits of entertainment, social networks, the dissemination of information by audiovisual means, calls and videoconferences over long distances, live broadcasts, among other things. Concretely, one of the services for the dissemination of current multimedia content, and quite popular worldwide, is the video streaming service. The video streaming consists in a technology of digital diffusion of multimedia content through a computer network, so that the users of the service are able to consume the product at the same time as it is downloaded. Making use of the current multimedia broadcasting technology and the development of web systems, in this thesis project the implementation of an Infochannel using web services for the visualization of multimedia content for the public institution ECU 911 of the city of Loja is proposed. The objective of this system is to facilitate the administration of institutional information content, specifically institutional videos, by means of a centralized system of control and dissemination of multimedia content taking advantage of the LAN network of the building. The development of the system was carried out taking into account the criteria of affluent video transmission, video coding and the use of free software tools for the development of web applications. In this paper we analyze certain basic technologies for the implementation of the system, such as Python, HTML5, CSS3 and JavaScript, such as programming languages, Apache as a web server, MySQL for database management, and the Django Framework as a nexus. of all these development technologies. Through the use of these tools, a multimedia diffusion system based on web services was achieved, consisting basically of two types of interfaces, one of control and administration of content, and the second as a user interface and visualization.